PELATIHAN MEMBUAT KOMPOS SECARA KONVENSIONAL DARI SAMPAH ORGANIK DOMESTIK DI KELURAHAN SUNGAI BINJAI KECAMATAN BATHIN III KABUPATEN BUNGO: TRAINING FOR CONVENTIONAL COMPOST FROM DOMESTIC ORGANIC WASTE IN SUNGAI BINJAI SUB-DISTRICT, BATHIN III DISTRICT, BUNGO DISTRICT - Pitriani; Isyaturriyadhah; Asnawati Is; Fikriman; Evo Afrianto (Fakultas Pertania Universitas Muara Bungo, 2023)
Compost is made from organic waste such as leaves from gardens, straw, grass, and leftover vegetable and fruit originating from household and market activities (domestic waste). Compost is made from market waste, both dry and wet waste. all materials that have a high nutrient content for plants, especially the macro elements N, P, and K. The purpose of this community service is that this activity is to carry out composting activities or make compost conventionally from domestic organic waste so as to be able to create new innovations that can provide added value to society and government. The results of community service, namely conventional composting or composting activities from domestic organic waste are as follows: Material preparation, Crushing or cutting, Setting layers, adding wet ingredients, Adding additional layers, Maintenance of moisture, Turning and mixing, Monitoring and adjustment, Compost ripening and Use of compost. Compost using green waste and brown waste (food scraps, dry leaves, grass, litter, plant clippings, and other organic matter). Keywords: Compost, Organic Waste, conventional.